Aesthetic Management of an Unerupted Maxillary Central Incisor with a Closed Eruption Surgical Technique: A Case Report - Kamrul Hasan, Md; Rahman Tani, Rokeya; Munir Khan Nabil, Mohsin; Rahman, Samira (Medicine Today, 2023)
Introduction: Treatment of impacted teeth requires a combination of orthodontics and surgery. Case report: Reported case is of a 12-year-old-girl with an unerupted maxillary central incisor obstructed by an odomtome. Discussion: Surgical exposure was done and traction with closed eruption technique was used. Result: The tooth was aligned in the dental arch with accepted aesthetic and functional satisfaction of the patient. Medicine Today 2023 Vol.35(2): 134-136